Comparison of efficacy of fluidotherapy and paraffin bath in hand osteoarthritis: A randomized controlled trial - Adil ÖNCEL; Sami KÜÇÜKŞEN; Hilal ECESOY; Emre SODALI; Şevket YALÇIN (Archives of Rheumatology, 2021)
Objectives: This study aims to compare the efficacy of paraffin bath therapy and fluidotherapy on pain, hand muscle strength, functional status, and quality of life (QoL) in patients with hand osteoarthritis (OA). Patients and methods: This prospective randomized controlled study included 77 patients (8 males, 69 females; mean age: 63.1±10.3 years; range 39 to 88 years) with primary hand OA who applied between July 2017 and March 2018. The patients were randomized into two groups with the sealed envelope method: Paraffin bath therapy (20 min, one session per day, for two weeks) was applied for 36 patients whereas 41 patients received fluidotherapy for the same period. The pain severity of the patients, both at rest and during activities of daily living (ADL) within the last 48 hours was questioned and scored using Visual Analog Scale. Duruöz Hand Index (DHI) was used to evaluate hand functions. Gross grip strength was measured using Jamar dynamometer whereas fine grip strength was measured using pinch meter in three different positions (lateral pinch, tip pinch, and palmar pinch). The 36-Item Short Form (SF-36) was used to analyze the QoL. All measurements were performed before, immediately after, and three months after treatment. Results: Improvement was observed in pain score at rest and during ADL, DHI scores, gross and fine grip strengths, and SF-36 subscores in both groups after treatment. However, no significant difference was observed between the groups. Conclusion: Both fluidotherapy and paraffin bath therapy have been found to have positive effects on pain, hand muscle strength, functional status, and QoL in the treatment of hand OA. However, no superiority was observed between the two treatment modalities.